2016
DOI: 10.1161/circimaging.116.005189
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Perfusion Improves Diagnostic Power of Coronary Computed Tomographic Angiography in Women

Abstract: Coronary computed tomographic angiography (CTA) has high sensitivity and excellent negative predictive value to Background-Coronary computed tomographic angiography (CTA) and myocardial perfusion imaging (CTP) is a validated approach for detection and exclusion of flow-limiting coronary artery disease (CAD), but little data are available on gender-specific performance of these modalities. In this study, we aimed to evaluate the diagnostic accuracy of combined coronary CTA and CTP in detecting flow-limiting CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Te assessment of coronary stenosis may exhibit some diferences between CAG and CCTA. Tis variation depends on factors such as the patient population, operator experience, and technological nuances [27,28]. We need to carefully consider these factors for a more accurate evaluation of coronary artery health.…”
Section: Discussionmentioning
confidence: 99%
“…Te assessment of coronary stenosis may exhibit some diferences between CAG and CCTA. Tis variation depends on factors such as the patient population, operator experience, and technological nuances [27,28]. We need to carefully consider these factors for a more accurate evaluation of coronary artery health.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of coronary computed tomographic angiography (CTA) and perfusion (CTP) imaging is more powerful in diagnosing flow-limiting stenosis than CTA or CTP alone. Also, CTP is superior to CTA in females [15].…”
Section: Diagnosismentioning
confidence: 90%
“…While some studies report similar accuracy of CTCA in detecting CAD in women and men, other studies have reported less sensitivity (54%-56% vs 85%-89%) and specificity (75% vs. 90%) in detecting CAD affecting distal coronary segments or side branches likely due to women having smaller epicardial arteries compared with men. [42][43][44] The PROMISE trial randomized patients with symptoms suggestive of stable CAD to either functional or anatomic testing. 45 There was no difference in clinical events between groups or by sex.…”
Section: Obstructive Cadmentioning
confidence: 99%